Pre- and Post-Occupancy Evaluation of Resident Motivations for and Experiences of Establishing a Home in a Low-Carbon Development - Breadsell, Jessica; Byrne, Joshua; Morrison, Gregory (2019)
There is some understanding of how an individual’s daily practices consume resources in the home, but the home as a space itself and peoples’ relationships to it remain an interesting research area. In this paper, residents of an Australian low-carbon development (LCD) are studied in order to discover the expectations and motivations driving them to move to their new home, the emotional landscape of the home, and their subsequent experiences living in an LCD. This exploration through mixed methods and a post-occupancy evaluation enables a longitudinal empirical study of the motivations, perceptions, expectations and experiences of an LCD residence. This study aims to further conceptualize the social understanding of a home and what people consider when moving into an LCD, along with the post-occupancy experiences that are important for establishing LCDs in the future. The results show that a home is associated with being a place of community, sustainability, safety and comfort, as well as a place that incorporates aesthetically pleasing features. The motivation for residents moving into an LCD is to have housing stability, live the life they want (including performing sustainable practices) and enjoy the attractive design of the LCD. The user experiences of living in an LCD include unexpected design influences on daily practices and an appreciation of the community atmosphere created. The strong sense of community and the self-reported thermally comfortable homes met residents’ expectations post-occupancy. This research is of interest to academics in the low-carbon and social science sectors, real-estate agents and property developers, as it provides insight into motivations and expectations of low-carbon dwelling residents.